Empowering through information literacy in secondary school libraries: a qualitative exploration of teachers’ perceptions through school librarians - Oluwole Durodolu; Joseph M. Ngoaketsi; Bolaji David Oladokun (AIB Studi)
This qualitative study investigates the perspectives of secondary school teachers regarding the roles and services of libraries and librarians in fulfilling their information needs. By conducting interviews and analyzing direct responses, several key themes emerge, including the suitability of libraries for teachers, perceptions of librarians as partners in the classroom, independent utilization of library resources, satisfaction with library services, understanding of the library's role in meeting information needs, perceptions of teachers' information literacy, and views on library responsibilities. The analysis reveals an overall positive sentiment towards libraries among teachers, who perceive them as conducive environments for tasks such as lesson preparation. However, there are mixed perceptions regarding the extent of partnership between teachers and librarians, as well as variations in the degree of independent use of library resources. While some teachers express satisfaction with library services, others suggest areas for improvement. Additionally, there are differing views on the library's role in addressing information needs, highlighting the necessity for libraries to adapt to evolving information landscapes. Furthermore, the study underscores mixed perspectives on teachers' information literacy skills, emphasizing the ongoing need for assessment and professional development. Lastly, perceptions of the library's responsibilities vary among teachers, emphasizing the multifaceted roles libraries play in supporting teaching and learning. In summary, this qualitative exploration offers valuable insights into teachers' perceptions of libraries and librarians, stressing the importance of understanding and addressing their needs and expectations to enhance collaboration and support for educators.